Model for resonant photon creation in a cavity with time-dependent conductivity - Crocce, Martín (2004)
A simple scalar model to mimic photon creation induced by time-dependent changes in the conductivity of a thin semiconductor was studied. It was found that in an electromagnetic cavity, photon can be created from the vacuum state by changing the cavity's properties with time. The time dependence was achieved by irradiating periodically the film with contained in the cavity. It was also observed that this time dependence may be achieved by irradiating periodically the film with short laser pulses.